Analysis of the interdiffusion of resin monomers into pre-polymerized fiber-reinforced composites - Wolff, Diana; Ding, Paul Georg Friedrich; Staehle, Hans Jörg; Frese, Cornelia (Dental materials, 2012)
Objectives The aim of the study was to analyze the dissolving depth of adhesive resin monomers into pre-polymerized fiber-reinforced composites (FRC) with either a semi-interpenetrating polymer network (semi-IPN) or a cross-linked polymer (CLP) matrix.MethodsFive unidirectional FRCs were tested, including one semi-IPN FRC (everStick® C&B, StickTech, (ES)) and four CLP-FRCs (GrandTec®, VOCO, (GT); Dentapreg®, ADM, (DP); TenderFiber®, Micerium, (TF); Splint-It®, Pentron Clinical Technologies, (SI)). The FRCs were light-polymerized following manufacturers’ instructions: the oxygen inhibition layers were removed and the adhesive resin (Optibond-FL®, KerrHawe) was labeled with a fluorescent dye (Rhodamine-B-isothiocyanate), which was then applied to the FRCs (5min) and light-polymerized (40s). Specimens were then prepared for confocal laser scanning microscopy. Three FRC strands per group were sectioned orthogonally to the direction of fibers, thus forming nine slices in each group. Four images were taken from each slice and the depths of adhesive penetration were measured in four sites per image (n=144 measurements per group).SignificanceDissolving depths were 17.28 (3.04)μm (ES), 12.58 (2.94)μm (SI), 7.57 (1.91)μm (TF), 3.27 (0.73)μm (DP) and 2.55 (0.63)μm (GT). Samples were normally distributed. Differences between groups were analyzed by ANOVA (PostHoc Scheffé) showing four subgroups (p=0.05). The infiltration layers detected were either continuous/homogenous (ES, TF, DP GT) or discontinuous/insular (SI).ConclusionThe adhesive resin monomers were able to diffuse significantly deeper into pre-polymerized semi-IPN specimens than into CLP materials. Semi-IPN specimens showed a homogenous and comparatively deeper layer of infiltration. The diffusion capabilities of secondary-IPN formation might increase the opportunity to establish a good bond between pre-polymerized FRC and new resin.
Gesehen am 08.10.2018